Influence of leadership styles on workplace deviant behaviours in the Nigerian Banking Industry - Philip Adekanmbi, Foluso; I Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2024)
This paper’s aim is to look into the influence of leadership styles on workplace deviant behaviours in the Nigerian banking industry. The paper adopted a quantitative research approach, which based a survey. Also, one non-probability sampling method and two probability sampling methods were used in the study, namely purposive, stratified, and simple random sampling, respectively. The empirical findings indicated a statistically significant moderate negative relationship between the transactional leadership style and workplace deviant behaviours in the Nigerian banking industry. Out of the two leadership styles (transformational and transactional), only transactional leadership style statistically significantly predicts workplace deviant behaviours negatively in the Nigerian banking industry. The outcome of the present study has a positive influence on the management of employees’ deviant behaviour in the Nigerian banking industry, as transactional leadership style was found to significantly reduce workplace deviant behaviours in the Nigerian banking industry. Hence, the Nigerian banking industry can minimise workplace deviant behaviours through a constant adoption of transactional leadership style.This investigation is distinctive, as it significantly contributes to scientific knowledge, in terms of identifying an appropriate leadership style(s), new strategies of reducing workplace deviant behaviours, and how leadership styles relate to workplace deviant behaviours, specifically in Nigeria’s banking industry. Hence, this research has highlighted the benefits of utilising a transactional leadership style in reducing workplace deviant behaviours